Strategies for Managing Childhood Obesity in Primary Schools in the Cape Coast Metropolis of Ghana - Whyte, Nancy Sekyi; Amissah, Augustina Araba; Mensah, Justice (Asian Journal of Contemporary Education, 2020)
Childhood obesity is a critical global public health issue due to its association with psychological, social, economic and health problems. This study explored the potency of using teachers in managing childhood obesity among primary school pupils in a Ghanaian Metropolis, Cape Coast. Structured questionnaire were used for data collection. A multi-stage sampling procedure was used to select 133 teachers as respondents for the study. Analyses were done using descriptive statistics (frequencies, percentages, means and standard deviations. The study revealed that teachers were appreciably aware of and had useful perceptions of childhood obesity which could be built upon by way of interventional strategies to curb obesity among the school pupils.. These included physical activity-based strategies and dietary-based strategies such as: children being allowed to play and run around during break periods (91.7%); no foods, sweets and drinks being allowed in the classroom during lessons (84.1%); and existence of a school policy that guides the type of foods sold on school premises (72.0%). However, the teachers needed to be supported to effectively manage the phenomenon in the school environment. School authorities could develop policies on sale of food and snacks on school premises and ensure adherence to the policies through strict enforcement.